Sleep disturbance and psychiatric disorders - Freeman, Daniel; Sheaves, Bryony; Waite, Felicity; Harvey, Allison G; Harrison, Paul J (The Lancet. Psychiatry, 2020)
Signs of mental ill health that cut across psychiatric diagnostic categories at high rates are typically viewed as non-specific occurrences, downgraded in importance and disregarded. However, problems not associated with particular diagnoses should be expected if there is shared causation across mental health conditions. If dynamic networks of interacting symptoms are the reality of mental health presentations, then particularly disruptive and highly connected problems should be especially common. The non-specific occurrence might be highly consequential. One non-specific occurrence that is often overlooked is patients' chronic difficulty in getting good sleep. In this Review, we consider whether disrupted sleep might be a contributory causal factor in the occurrence of major types of mental health disorders. It is argued that insomnia and other mental health conditions not only share common causes but also show a bidirectional relationship, with typically the strongest pathway being disrupted sleep as a causal factor in the occurrence of other psychiatric problems. Treating insomnia lessens other mental health problems. Intervening on sleep at an early stage might be a preventive strategy for the onset of clinical disorders. Our recommendations are that insomnia is assessed routinely in the occurrence of mental health disorders; that sleep disturbance is treated in services as a problem in its own right, yet also recognised as a pathway to reduce other mental health difficulties; and that access to evidence-based treatment for sleep difficulties is expanded in mental health services.